2005
DOI: 10.1016/j.jtcvs.2004.12.050
|View full text |Cite
|
Sign up to set email alerts
|

High-dose radiotherapy in trimodality treatment of Pancoast tumors results in high pathologic complete response rates and excellent long-term survival

Abstract: Surgical resection of Pancoast tumors after neoadjuvant high-dose radiation and chemotherapy can be safely performed. High-dose radiation in trimodality treatment is well tolerated and might be beneficial. Similar to other studies, late central nervous system relapse is problematic and indicates a need for assessing the role of prophylactic cranial irradiation in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 15 publications
(16 reference statements)
3
56
1
1
Order By: Relevance
“…Even long-term (5-year) survival rates resulted improved reaching 44% (SWOG 9416) and 56% (JCO 9806), respectively. Based on these data, the modern standard treatment for sulcus superior tumors has become the combination of induction CT/RT followed by radical surgical resection (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43) (Table 1).…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Even long-term (5-year) survival rates resulted improved reaching 44% (SWOG 9416) and 56% (JCO 9806), respectively. Based on these data, the modern standard treatment for sulcus superior tumors has become the combination of induction CT/RT followed by radical surgical resection (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43) (Table 1).…”
Section: A B Cmentioning
confidence: 99%
“…Operative mortality rate ranges from 0% to 6.9% and morbidity from 11% to 47% (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43). In particular, the SWOG 9416 (35) and JCO 9806 (36) phase II trials showed operative mortality rates of 2.3% and 3% and morbidity rates of 52% and 14%, respectively.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…En-bloc resection of the upper lobe, ribs, nerves (brachial plexus) plus or minus vessels is recommended. Many studies published in the past 10 years have established the gold standard in the field as induction therapy consisting of high dose radiotherapy with concurrent cisplatin-based chemotherapy, followed by surgery 4-6 weeks later [124][125][126][127][128][129]. Using this multimodality scheme, perioperative mortality is low and 5-year survival rates are now consistently .40%.…”
Section: Superior Sulcus Tumours (Pancoast Tumours)mentioning
confidence: 99%
“…Recent studies have shown that complete response to induction therapy was a significant predictive factor for overall survival [124][125][126]. Late central nervous system relapse remains a problem and the role of PCI should be evaluated in this group of patients [129].…”
Section: Superior Sulcus Tumours (Pancoast Tumours)mentioning
confidence: 99%